Application of surplus and waste materials in roads pavement making - Mousavi, S. M.; Fazli, A. H.; Rouzmehr, F. (Видавництво Львівської політехніки, 2011)
Nowadays there are a lot of problems about surpluses and debris made by humans all around the world. Lots of these surpluses seriously harm our natural environment. Reuse of this kind of materials in other processes like building constructions or pavement help our natural environment in every aspect. Asphalt concrete is the main part of pavements in most parts of the world with an increasing rate of production in need of more ways and roads. In this paper we will provide the latest conclusions of using these kinds of materials in making asphalt concrete and their impact on its properties. Some of these materials investigated in this article are,fragmented glass,plastic,rubber,construction debris,electronic debri and heavy polyethylene debris. And at the end we will provide some proposals to making the optimum kind of asphalt concrete using these materials and will investigate the impact of using such material on economical an environmental conditions of countries.
Застосування надлишкових матеріалів і відходів при влаштуванні дорожнього покриття
Keywords: surplus materials; reusable materials; asphalt concrete; pavement; natural environment